SPEECH CHARACTERISTICS OF JOURNALISTIC TEXTS; JOURNALIST’S SPEECH CULTURE - M. Avakyan (International Journal of Innovative Technologies in Social Science, 2021)
The paper examines such notions as speech characteristics of journalistic texts, journalist’s speech culture, and its compliance with the language structure of the current language norms. Today a general tendency of deterioration of speech culture in the public may be observed. Such a situation may be explained by “freedom of speech” which today is perceived literally rather than figuratively. However, the language of mass media is a key factor to the formation of not only speech but also mental culture.